53.5k views
2 votes
Ben solved an equation as shown below, Equation 2 (-3×+1)=9×-8. what did he do wrong. step1. -6×+2=9×- 8. step2. -6×+9×=-8+2. step3. 3x=-6. step4. x=-2

User Abbr
by
5.1k points

2 Answers

3 votes

failed to evaluate 9 × - 8

2( - 3x + 1) = 9 × - 8

- 6x + 2 = - 72 ( subtract 2 from both sides )

- 6x = - 74 ( divide both sides by - 6 )

x =
(-74)/(-6) =
(37)/(3)



User Shengy
by
5.7k points
2 votes
He just switched sides of the variables and numbers. Instead if adding the opposite.
User Srh
by
5.7k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.